2008
DOI: 10.1242/jcs.023150
|View full text |Cite
|
Sign up to set email alerts
|

A new model for hemoglobin ingestion and transport by the human malaria parasite Plasmodium falciparum

Abstract: The current model for hemoglobin ingestion and transport by intraerythrocytic Plasmodium falciparum malaria parasites shares similarities with endocytosis. However, the model is largely hypothetical, and the mechanisms responsible for the ingestion and transport of host cell hemoglobin to the lysosome-like food vacuole (FV) of the parasite are poorly understood. Because actin dynamics play key roles in vesicle formation and transport in endocytosis, we used the actin-perturbing agents jasplakinolide and cytoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
108
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(118 citation statements)
references
References 68 publications
9
108
1
Order By: Relevance
“…Two recent studies of DV genesis and haemoglobin uptake processes used serial thin section electron microscopy Lazarus et al, 2008). However, because of the huge amount of work involved in this very challenging technique, these studies were restricted to reconstruction of a limited cell depth or of a few whole cells.…”
Section: Haemoglobin Uptake and Degradation Is Initiated In Early Stamentioning
confidence: 99%
See 2 more Smart Citations
“…Two recent studies of DV genesis and haemoglobin uptake processes used serial thin section electron microscopy Lazarus et al, 2008). However, because of the huge amount of work involved in this very challenging technique, these studies were restricted to reconstruction of a limited cell depth or of a few whole cells.…”
Section: Haemoglobin Uptake and Degradation Is Initiated In Early Stamentioning
confidence: 99%
“…Another study examined the ultrastructure of the endocytic apparatus and concluded that haemoglobin uptake occurs by a vesicle-independent process (Lazarus et al, 2008). These authors reported that cytostomal invaginations elongate to form tubes that appose the DV but remain connected to the parasite surface and open to the RBC cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,26 Similarly, tumor cell lysosomes degrade damaged organelles or bulk proteins for amino acid and energy recycling via the autophagy pathway. 8 Quinoline-based antimalarial compounds, such as CQ, hydroxychloroquine (HCQ), quinine (QN), mefloquine (MFQ), and quinacrine (QNX), are mainstay therapies that effectively kill P. falciparum parasites.…”
mentioning
confidence: 99%
“…The second phase, the 'trophozoite stage' , is characterized by rapid parasite growth and the appearance of haemozoin (remnant of digested haemoglobin) in the food vacuole (FV). The mode of haemoglobin internalization is still debated and might include several distinct processes [7][8][9] . Finally, the parasite enters the 'schizont stage' during which it generates up to 32 daughter merozoites that, after rupture of the host cell, invade new erythrocytes.…”
mentioning
confidence: 99%